2001
DOI: 10.1359/jbmr.2001.16.5.901
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Osteoporosis Based on Bone Mineral Densities

Abstract: In this article we examine the role of bone mineral density (BMD) in the diagnosis of osteoporosis. Using information from 7671 women in the Study of Osteoporotic Fractures (SOF) with BMD measurements at the proximal femur, lumbar spine, forearm, and calcaneus, we examine three models with differing criteria for the diagnosis of osteoporosis. Model 1 is based on the World Health Organization (WHO) criteria using a T score of ؊2.5 relative to the manufacturers' young normative data aged 20 -29 years, with modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
81
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(89 citation statements)
references
References 21 publications
6
81
0
2
Order By: Relevance
“…(20,20,21) Also in accord with earlier studies, our results show that an increase in the number of osteoporotic sites predicts a higher risk of incident fractures. (21,22,20) For example, in one large clinical referral population, the age-adjusted risk of any osteoporotic fracture ascertained from administrative records increased as the number of osteoporotic sites (total hip, femoral neck, trochanter, or lumbar spine) increased. (20) This association was eliminated by adjustment for total hip BMD as a continuous risk factor.…”
Section: Discussionsupporting
confidence: 92%
“…(20,20,21) Also in accord with earlier studies, our results show that an increase in the number of osteoporotic sites predicts a higher risk of incident fractures. (21,22,20) For example, in one large clinical referral population, the age-adjusted risk of any osteoporotic fracture ascertained from administrative records increased as the number of osteoporotic sites (total hip, femoral neck, trochanter, or lumbar spine) increased. (20) This association was eliminated by adjustment for total hip BMD as a continuous risk factor.…”
Section: Discussionsupporting
confidence: 92%
“…BMD measurements are commonly done by central DXA of the spine and hip. Peripheral BMD measurements with non-DXA techniques at the heel, forearm or hand are performed less commonly and their results correlate only poorly with central DXA 19 . The power of BMD to predict fracture risk at different sites, however, is improved by site-specific measurements, and hip or spine BMD predict forearm fracture risk less well than peripheral BMD 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that lack of agreement between central and peripheral DEXA is a barrier to recommending peripheral DEXA scan methods. 28,29 In the same context, Wigderowitz et al 30 examined the extent to which patients with Colles' fractures have osteopenia. They measured BMD in the contralateral radius of 235 women ranging from 21 to 92 years in age presenting with Colles' fractures over a 2-year period.…”
Section: Discussionmentioning
confidence: 99%